ANALISIS PENINGKATAN EFEKTIVITAS BONGKAR MUAT KOMODITAS DI PELABUHAN CIGADING - CILEGON - Restrinanda Syifaani, (2022)
Initially, the port was functioned to be a support or edge so that ships and boats could be moored for activities such as ferrying, unloading, and other simple activities. With the development of the social and economic life of the population, the facilities of the port continue to grow until the very day. The port is a very important facility in the loading and unloading process. The purpose of this study is to analyze the effectiveness in the implementation of unloading rainfall using port service performance indicators in the form of Effectiveness (ET) and Productivity (Q/J). From this data, it was found that there was a decrease in the Effective Time (ET) and Productivity (Q/A) in 2019 and an increase in 2020. Some suggestions that can be given to increase the effectiveness of loading and unloading at Cigading Port are the addition of 2 (two) Ship Unloader units, conducting periodic checks and scheduled maintenance on loading and unloading facilities, re-certifying the crane operator capabilities, collaborating with BMKG for weather conditions, the addition of port jetty area and the addition of a monitoring post near the open gate area.